Foundations for performance training : skills for the actor-dancer - Harker, Cara (Routledge, 2022)
"Foundations for Performance Training: Skills for the Actor-Dancer explores the physical, emotional, and theoretical components of performance training in order to equip readers with the tools needed to successfully advance in their development as artists and entertainers. Each chapter provides a fresh perspective on subjects that students of acting and dance courses encounter throughout their development as performing artists. Topics include: Equity, diversity, and inclusion in performance; Mind/body conditioning for training, rehearsal, and performance; Developing stage presence and spatial awareness; Cultivating motivation and intention in performance; Expanding repertoire and broadening skillset for performance; Auditioning for film and stage; Developing theatrical productions. This book also offers experiential exercises, journal writing prompts, and assignments to engage readers, enrich their learning experience, and deepen their exploration of the material described in each chapter. Readers will grow as performing artists as they analyze the principles of both acting and dance and discover how deeply the two art forms are intertwined. An excellent resource for students of acting, musical theatre, and dancing courses, Foundations for Performance Training encourages a strong foundation in creative analysis, technique and expression, and self-care to cultivate excellence in performance"--